UJI BEBERAPA URINE HEWAN TERNAK PADA PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.)DI PEMBIBITAN UTAMA - Givo Alzeri; Sampurno '; Murniati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objectives of this study was todetermine the influence ofsomelivestockurineto the growth of oil palmandgetthe best forthe growth ofoil palminthe mainnursery. Study has beencarried outinthe land of Plant Laboratory, Agriculture Faculty,University of RiaufromFebruary to May2014. Thisstudy arranged experimentally using Completely Randomized Design(CRD), consistof5 treatmentsandeach treatmentwas repeated4times then obtained20experimental units, while thetreatment givenisurinelivestockconsistof:sheep urine, goaturine,buffalo urine, horseurineandcow urine. Parametersmeasured were: the increment of seeds height, increment of hump diameter, increment ofleafmidrib,root length, root volume, rootcrownratioanddry weightof seedlings. Data were analyzedusingANOVAandfollowed byfurther Different Real Honest (DRH)testat5% level. From the study thathas beencarried out, showthat thegiving ofurineofdifferenttypes oflivestockonoil palm seedshowedsignificant effecton the overall observed parameters. Treatmentgoat urine showedthe best resultsforall parametersobserved. Comparedwiththe growth of oil palmseedstandardseven-month-old,goaturine and sheep urineturnsgivingexceeding thegrowth of oil palmseedinseeds height, hump diameterandnumber ofleaf midrib. Keywords: Livestock urine, oil palm, main nursery